Increasing the level of preparedness of 400 m hurdles runners by means of hypoxic exposure as the basis for achieving a sporting result - Гребенюк, Олег (Slobozhanskyi Herald of Science and Sport, 2018)
Oleg Grebeniuk Purpose: establish the dependence of the result of 400 m hurdles on the morphofunctional, physical and hypoxic preparedness of athletes. Material & Methods: the study involved 18 athletes aged 16–18 years who had the level of preparedness of the first sports category and the candidate master of sports in the 400 m hurdles. To establish the role of hypoxic training in increasing anaerobic performance, multiple regression analysis was used, which determines the role of each factor in the adaptation mechanism, as well as in the performance of test tasks. Results: determined the importance of training physical qualities, morphofunctional abilities, hypoxic stability for the successful manifestation of technical skill in competitive conditions. Conclusions: the inclusion in the training process of interval hypoxic training contributed to a more significant increase in the anaerobic performance of 400 m hurdles runners.